Magnesium alloy hollow bone screw and preparation method thereof
By using Mg-Zn-Mn alloy and rolling processing to form continuous fine crystal zones and setting a composite coating on the surface, the problem of rapid degradation and poor corrosion resistance of magnesium alloy hollow bone screws in the body is solved, and strength improvement and stable degradation are achieved to meet the needs of fracture healing.
Patent Information
- Application Number
- CN202411854698.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
AI Technical Summary
Existing magnesium alloy hollow bone screws are prone to rapid degradation in the internal environment, resulting in insufficient mechanical strength, affecting the stability and biosafety of fracture healing, and at the same time, their corrosion resistance is also poor.
A magnesium alloy hollow bone screw made of Mg-Zn-Mn alloy is formed by rolling processing to form a continuous fine crystal region, and a composite coating composed of Zn/Mg-HA calcium and phosphorus layer and a parelin layer are provided on the surface.
It improves the strength and corrosion uniformity of magnesium alloy materials, extends the mechanical support time of the implant in the body, enhances corrosion resistance and adhesion, ensures stable degradation of the screws, and cooperates with the healing of bone tissue.
Smart Images

Figure CN119679493A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of medical auxiliary equipment, and in particular to a magnesium alloy hollow bone screw and a preparation method thereof. Background Art
[0002] As an absorbable metal material, magnesium and its alloys excel in biocompatibility and mechanical properties. They can naturally degrade in the body, avoiding the need for secondary surgery and significantly reducing the burden on patients. In addition, the elastic modulus of magnesium alloys is close to that of human bones, which can effectively reduce the "stress shielding" effect. Magnesium ions, the degradation product of magnesium, can promote bone regeneration and integration, and help bone healing. These characteristics give magnesium alloys broad application prospects in orthopedic implant materials.
[0003] The strength of magnesium alloy itself is not high. After being processed into hollow screws, it is easy to degrade rapidly and produce hydrogen in the body environment. The insufficient mechanical strength is easy to lose the fixation strength, affecting its stability and biosafety in fracture healing. Therefore, magnesium alloy hollow screws still face great challenges in practical clinical application.
[0004] Most of the existing magnesium alloys are added with Zn, Al or rare earth elements, and then the magnesium alloy hollow screws are obtained by alloying smelting, forging, extrusion, turning, additive manufacturing and other means. The tensile strength is mostly below 300MPa, and the elongation at break is mostly less than 15%, which cannot meet the requirements of high strength and high plasticity of magnesium alloy hollow screws.
[0005] For the corrosion resistance of magnesium alloy hollow screws, surface treatment is an important means to optimize the degradation behavior. By applying a coating with excellent biocompatibility on the surface of the magnesium alloy, its corrosion rate can be effectively slowed down and the mechanical support time of the implant in the body can be prolonged. Currently, the coatings that improve corrosion performance are mostly HAP coatings. A layer of inorganic protective coating is prepared on the surface of the magnesium alloy by physical coating or electrochemical methods to isolate the magnesium metal material from body fluids to improve the corrosion resistance of the magnesium metal.
[0006] Although the alloying of the above-mentioned existing magnesium alloys has solved the problem of the strength of magnesium alloys to a certain extent, the presence of a large amount of second phases inside leads to uneven stress distribution during processing and the formation of micro-batteries with the base magnesium, which causes the corrosion of the magnesium alloy screws after implantation to be aggravated; at the same time, the existing magnesium alloy hollow bone screws do not have high mechanical properties due to their hollow structure, processing method, and thin wall thickness. In particular, the stressed parts (such as nuts and threads) will experience local premature fractures, twisting or cracks due to corrosion degradation during long-term use.
[0007] Although HAP coating has good biocompatibility, it is not dense and has poor adhesion, so it can only provide protection for magnesium alloy in the short term. Body fluid corrosion and coating peeling will occur soon after implantation, the corrosion rate will increase again, and the screw performance will be quickly lost.
[0008] In order to solve the problems of poor corrosion resistance and insufficient mechanical properties of magnesium alloy screws, a new type of magnesium alloy hollow bone screw and a preparation method thereof are provided. Summary of the invention
[0009] In order to overcome the above-mentioned defects of the prior art, the present invention provides a magnesium alloy hollow bone screw and a preparation method thereof to solve the problems existing in the above-mentioned background technology.
[0010] The present invention provides the following technical solution: a magnesium alloy hollow bone screw, which includes a screw head, a screw body, and a screw tail, and is characterized in that: the screw is made of Mg-Zn-Mn alloy, wherein the Zn content is 1.2%-1.8%, the Mn content is 0.05%-0.08%, and the rest is pure magnesium, the surface microstructure of the screw is a continuous fine grain zone formed after rolling treatment, and the surface of the screw is provided with a composite coating (4) consisting of a Zn / Mg-HA calcium-phosphorus layer and a parylene layer.
[0011] Preferably, a hollow structure is provided inside the screw body and the screw tail, and a screwing groove is provided at the front end of the screw head (1).
[0012] A method for preparing a magnesium alloy hollow bone screw comprises the following steps:
[0013] S1. Obtaining a magnesium alloy rod-shaped ingot and subjecting it to a thermomechanical treatment to a desired size for processing;
[0014] S2. rolling the magnesium alloy tube at room temperature to avoid softening of the magnesium alloy;
[0015] S3. Drilling a hole inside the magnesium alloy screw to a depth equal to the length of the screw to form a hollow hole inside the screw;
[0016] S4. Clean the magnesium alloy hollow bone screw to remove residues;
[0017] S5. Prepare a surface treatment solution, wherein the surface treatment solution includes magnesium nitrate hexahydrate, zinc nitrate hexahydrate and calcium nitrate tetrahydrate, EDTA-4NH4, alanine, diammonium hydrogen phosphate, and ammonia water. After the preparation is completed, place the cleaned sample in the treatment solution and heat it in a 60°C water bath for 4-6 hours. After the reaction is completed, take it out and wash it.
[0018] S6. Deposit another layer of parylene on the surface treatment layer using a deposition method, and then perform low-temperature annealing to improve adhesion
[0019] Preferably, the composition of the magnesium alloy rod-shaped ingot includes 1.2%-1.8% Zn, 0.05%-0.08% Mn, and the rest is pure magnesium.
[0020] Preferably, the rolling temperature is 50-100° C., the rolling force is 3-6 tons, the rolling speed is 0.1-1 mm / min, and dithiophosphate lubricant is selected for rolling, and the rolling is performed in one step to ensure the consistency and accuracy of the thread.
[0021] Preferably, during drilling, the tool speed is 600-1200 rpm and the feed speed is 0.01-0.1 mm / rev.
[0022] Preferably, during preparation, 0.02-0.18 mol / L magnesium nitrate hexahydrate, 0.18-0.02 mol / L zinc nitrate hexahydrate and 0.8 mol / L calcium nitrate tetrahydrate are added to water and stirred until completely dissolved to form a uniform mixed solution, 1 mol / L EDTA-4NH4 and 2 mol / L alanine are gradually added to the solution and stirred until completely dissolved to ensure that Ca 2+ 、Zn 2+ and Mg 2+ Chelate with EDTA to regulate the release of metal ions, then slowly add the prepared 0.6 mol / L diammonium hydrogen phosphate solution to the mixed solution, maintain a magnetic stirring speed of 100-200 rpm during the addition process to ensure uniform mixing of the solution, and adjust the solution pH to 9-11 with ammonia water to obtain a surface treatment solution.
[0023] Preferably, the surface coating of the surface treatment solution is Zn / Mg-HAP doped with zinc and magnesium, and the compound is Ca 10 -x-yMgxZny(PO4)6(OH)2, wherein the ratio of magnesium nitrate hexahydrate, zinc nitrate hexahydrate, calcium nitrate tetrahydrate: EDTA-4NH4: alanine: diammonium hydrogen phosphate is 1:1:2:0.6.
[0024] Preferably, in the surface treatment solution, the ratio of magnesium nitrate hexahydrate, zinc nitrate hexahydrate, calcium nitrate tetrahydrate: EDTA-4NH4: alanine: diammonium hydrogen phosphate is 1:1:2:0.6, the concentration of magnesium nitrate hexahydrate is 0.02-0.2 mol / L, the concentration of zinc nitrate hexahydrate is 0.01-0.05 mol / L, the concentration of calcium nitrate tetrahydrate is 0.8-0.98 mol / L, the concentration of EDTA-4NH4 is 1 mol / L, and the concentration of alanine is 2 mol / L. The concentration of diammonium hydrogen phosphate solution is 0.4-0.6 mol / L.
[0025] Preferably, the thickness of the parylene layer is 0.1-1 um.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The outer surface structure of the screw of the present invention is plastically deformed by rolling to form a continuous fine-grained area. Compared with the grains of the material cut off by turning, the grain streamlines are interrupted, and the continuity of the material is not damaged. In the subsequent use process, the stress concentration is greatly reduced, and the local degradation of the screw is avoided. The screw fixation functionality is lost in the early stage of the degradation process, and the strength and corrosion uniformity of the magnesium alloy material are greatly improved.
[0028] 2. The surface of the screw of the present invention is provided with a composite coating consisting of a Zn / Mg-HA calcium-phosphorus layer and a parylene layer. Compared with the traditional HAP coating, zinc ions and magnesium ions replace calcium ions in hydroxyapatite and enter the HAP lattice, thereby increasing the lattice distortion and promoting the increase of grain boundaries. The added alanine can induce HA nucleation, improve the crystallinity, hinder the growth of HA crystals, and refine the grains. The porosity of the coating is reduced macroscopically, the stability is improved, and the strength is also higher. On the one hand, the corrosion resistance and adhesion of the magnesium alloy hollow bone screw can be better enhanced. On the other hand, more nucleation sites can enhance the bonding of parylene molecules, osteoblasts and the surface treatment layer.
[0029] 3. The coating used on the surface of traditional magnesium alloy bone screws only protects the screws in the early stage of degradation. Once the coating is porous or damaged, a large amount of body fluid enters the interior and begins to corrode the screws rapidly. The composite coating on the surface of the hollow bone screw of the present invention has high density and strong bonding force. The coating is stable for a long time and has a very small solution permeability. It can control the body fluid to slowly penetrate the coating to corrode the magnesium alloy for a long time, so that the screw can be degraded stably at a slow rate, which is in line with the healing of bone tissue in time. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a schematic diagram of the front view structure of the screw of the present invention.
[0031] Figure 2 It is a schematic diagram of the cross-sectional structure of the screw of the present invention.
[0032] Figure 3 This is a schematic diagram of the degradation and corrosion structure of Example 1 of the present invention after being implanted for three months.
[0033] Figure 4 This is a schematic diagram of degradation and corrosion after three months of implantation in Example 3 of the present invention.
[0034] Figure 5 This is a schematic diagram of the surface morphology of Example 3 of the present invention.
[0035] Figure 6 This is a schematic diagram of the surface morphology of Example 1 of the present invention.
[0036] The accompanying drawings are marked as follows: 1. screw head; 2. screw body; 3. screw tail; 4. composite coating; 5. hollow structure; 6. screw groove. DETAILED DESCRIPTION
[0037] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.
[0038] The present invention provides a magnesium alloy hollow bone screw, such as Figure 1 , 2 As shown;
[0039] The screw comprises a screw head 1, a screw body 2 and a screw tail 3. The screw is made of Mg-Zn-Mn alloy. The surface microstructure of the screw is a continuous fine grain zone formed after rolling treatment. The surface of the screw is provided with a composite coating 4 consisting of a Zn / Mg-HA calcium phosphate layer and a parylene layer.
[0040] A hollow structure 5 is provided inside the screw body 2 and the screw tail 3 , and a screwing groove 6 is provided at the front end of the screw head 1 .
[0041] The outer surface structure of the screw is plastically deformed by rolling to form a continuous fine-grained area. Compared with the grain cutting of the material by turning, the grain streamlines are interrupted and the continuity of the material is not damaged. In the subsequent use process, the stress concentration will be greatly reduced, avoiding the local degradation of the screw. The screw fixation functionality is lost in the early stage of the degradation process, which greatly improves the strength of the magnesium alloy material and the corrosion uniformity.
[0042] A composite coating consisting of a Zn / Mg-HA calcium-phosphorus layer and a parylene layer is set on the surface of the screw. Compared with the traditional HAP coating, zinc ions and magnesium ions replace the calcium ions in hydroxyapatite and enter the HAP lattice, increasing the lattice distortion and promoting the increase of grain boundaries. The added alanine can induce HA nucleation, improve the crystallinity, hinder the growth of HA crystals, and refine the grains. On a macro scale, the porosity of the coating is reduced, the stability is improved, and the strength is higher. On the one hand, it can better enhance the corrosion resistance and adhesion of the magnesium alloy hollow bone screw. On the other hand, more nucleation sites can enhance the bonding of parylene molecules, osteoblasts and the surface treatment layer.
[0043] The surface of the hollow bone screw adopts a composite coating composed of a Zn / Mg-HA calcium-phosphate layer and a parylene layer. Compared with the short-term protection of the traditional HAP coating before degradation, it has high density and strong bonding force. The coating is stable for a long time and has a very small solution permeability. It can control the body fluid to slowly penetrate the coating and corrode the magnesium alloy for a long time, so that the screw can be degraded stably at a slow rate, which is in line with the healing of bone tissue in time.
[0044] Example 1
[0045] The material of the magnesium alloy hollow bone screw is Mg-Zn-Mn alloy, with a Zn content of 1.2%, a Mn content of 0.05%, and the rest being magnesium. The microstructure on the surface of the screw is a continuous fine-grained area, and the corrosion process is uniform corrosion. The tensile strength of the magnesium alloy material is 343MPa, and the elongation at break is 31%. The surface of the screw is a composite coating composed of a Zn / Mg-HA calcium-phosphorus layer and a parylene layer, and the corrosion rate of the screw is 0.25mm / y.
[0046] The preparation method of the magnesium alloy hollow bone screw comprises the following steps:
[0047] S1. Obtaining a magnesium alloy rod-shaped ingot and subjecting it to a thermomechanical treatment to a desired size for processing;
[0048] S2. Roll the magnesium alloy tube at room temperature to avoid softening of the magnesium alloy. The rolling temperature is 50°C, the rolling force is 3 tons, and the rolling speed is 0.1 mm / min. Dithiophosphate lubricant is selected for rolling. The rolling is performed in one step to ensure the consistency and accuracy of the thread.
[0049] S3. Drilling the inside of the magnesium alloy screw at a speed of 600 rpm, a feed rate of 0.01 mm / rev, a drilling depth of the screw length, and forming a hollow screw internal channel;
[0050] S4. Clean the magnesium alloy hollow bone screw to remove residues;
[0051] S5. Prepare surface treatment solution: Add magnesium nitrate hexahydrate, zinc nitrate hexahydrate and calcium nitrate tetrahydrate to an appropriate amount of water, with final concentrations of 0.18 mol / L, 0.02 mol / L and 0.8 mol / L respectively, and stir until completely dissolved to form a uniform mixed solution. Then, add EDTA-4NH4 and alanine to the mixed solution in small amounts to make the final concentrations reach 1 mol / L and 2 mol / L respectively, and continue stirring until completely dissolved to ensure that the Ca in the solution is 2+ 、Zn 2+ and Mg 2+Fully chelate with EDTA, thereby effectively regulating the release of metal ions. Slowly add the pre-prepared 1.2 mol / L diammonium phosphate solution (the ratio of its volume to the current mixed solution volume is 1:1, and the final concentration of diammonium phosphate is 0.6 mol / L) to the mixed solution. During the addition process, maintain a magnetic stirring speed of 100 rpm to ensure uniform mixing of the solution. Finally, use ammonia water to adjust the pH value of the solution to 9. After the preparation is completed, place the cleaned sample in the solution and heat it in a 60°C water bath for 6 hours. After the reaction is completed, take it out and wash it.
[0052] S6. Deposit another layer of parylene on the surface treatment layer using a deposition method. The thickness of the parylene layer is 0.1 um, and then perform low-temperature annealing treatment to improve adhesion.
[0053] Example 2
[0054] The material of the magnesium alloy hollow bone screw is Mg-Zn-Mn alloy, with a Zn content of 1.8%, a Mn content of 0.08%, and the rest being magnesium. The microstructure on the surface of the screw is a continuous fine-grained area, and the corrosion process is uniform corrosion. The tensile strength of the magnesium alloy material is 341 MPa, and the elongation at break is 30%. The surface of the screw is a composite coating composed of a Zn / Mg-HA calcium-phosphorus layer and a parylene layer, and the corrosion rate of the screw is 0.23 mm / y.
[0055] The preparation method of the magnesium alloy hollow bone screw comprises the following steps:
[0056] S1. Obtaining a magnesium alloy rod-shaped ingot and subjecting it to a thermomechanical treatment to a desired size for processing;
[0057] S2. Roll the magnesium alloy tube at room temperature to avoid softening of the magnesium alloy. The rolling temperature is 100°C, the rolling force is 6 tons, and the rolling speed is 1 mm / min. Dithiophosphate lubricant is selected for rolling. The rolling is performed in one step to ensure the consistency and accuracy of the thread.
[0058] S3. Drilling the inside of the magnesium alloy screw at a speed of 1200 rpm, a feed rate of 0.1 mm / rev, a drilling depth of the screw length, and forming a hollow screw internal channel;
[0059] S4. Clean the magnesium alloy hollow bone screw to remove residues;
[0060] S5. Prepare surface treatment solution: Add magnesium nitrate hexahydrate, zinc nitrate hexahydrate and calcium nitrate tetrahydrate to an appropriate amount of water, with final concentrations of 0.1 mol / L, 0.01 mol / L and 0.89 mol / L respectively, and stir until completely dissolved to form a uniform mixed solution. Then, add EDTA-4NH4 and alanine to the mixed solution in small amounts to make the final concentrations reach 1 mol / L and 2 mol / L respectively, and continue stirring until completely dissolved to ensure that the Ca in the solution is 2+ 、Zn 2+ and Mg 2+ Fully chelate with EDTA, thereby effectively regulating the release of metal ions. Slowly add the pre-prepared 1.2 mol / L diammonium phosphate solution (the ratio of its volume to the current mixed solution volume is 1:1, and the final concentration of diammonium phosphate is 0.6 mol / L) to the mixed solution. During the addition process, maintain a magnetic stirring speed of 200 rpm to ensure uniform mixing of the solution. Finally, use ammonia water to adjust the pH value of the solution to 11. After the preparation is completed, place the cleaned sample in the solution and heat it in a 90°C water bath for 4 hours. After the reaction is completed, take it out and wash it.
[0061] S6. Deposit another layer of parylene on the surface treatment layer using a deposition method. The thickness of the parylene layer is 1 um, and then perform low-temperature annealing treatment to improve adhesion.
[0062] Example 3
[0063] The alloy hollow bone screw is made of Mg-Zn-Al alloy;
[0064] S1. Obtaining a magnesium alloy rod-shaped ingot and subjecting it to a thermomechanical treatment to a desired size for processing;
[0065] S2. Turning the magnesium alloy tube into a specified screw size at room temperature;
[0066] S4. Clean the magnesium alloy hollow bone screw to remove residues;
[0067] S5. Prepare a surface treatment solution, mix 0.25 mol / L diammonium hydrogen phosphate solution and 0.25 mol / L EDTA evenly, adjust the pH to 9-11, and heat it in a water bath at 80°C for 6 hours to prepare a common HAP surface treatment layer. Take out the screw, wash and dry it to prepare a magnesium alloy hollow bone screw with hydroxyapatite on the surface.
[0068] In accordance with the requirements of ASTM-G31 (2021), the magnesium alloy hollow bone screws of Examples 1, 2, and 3 were implanted into the leg bones of goats. Three months after implantation, the corrosion rates of the three magnesium alloy hollow bone screws were calculated by CT reconstruction results. The results are shown in Table 1.
[0069] Table 1: Average corrosion rate of the sample within three months
[0070]
[0071]
[0072] like Figure 3 , 4 As shown, in Example 1, three months after being implanted in a goat, the threads of the screw head 1 and the screw tail 3 are still clearly visible, the screw as a whole is uniformly degraded without breaking, and its fixation decays with degradation. Example 3 is a comparative example. Three months after the implantation of a traditional magnesium alloy screw, the threads of the screw head 1 and the screw tail 3 have become blurred and invisible, and the degradation differences in different parts of the screw are obvious. The screw body 2 has been degraded and broken, and the screw has lost its fixation, which does not meet the requirements of bone healing for screws.
[0073] like Figure 5 , 6 As shown, compared with the ordinary HA coating on the surface of Example 3, the Zn / Mg-HA calcium-phosphorus layer on the surface of Example 1 has much smaller coating grains than Example 3 at the same magnification. Therefore, the surface treated coating has higher nucleation degree and density and possesses higher corrosion resistance.
[0074] Several points should be explained: First, in the description of this application, it should be noted that, unless otherwise specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, which may refer to mechanical connection or electrical connection, or internal communication between two components, or direct connection. "upper", "lower", "left", "right", etc. are only used to indicate relative positional relationships. When the absolute position of the object being described changes, the relative positional relationship may change;
[0075] The above description is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiment. Any equivalent modifications or changes made by ordinary technicians in this field based on the contents disclosed by the present invention should be included in the protection scope recorded in the claims.
Claims
1. A magnesium alloy hollow bone screw, comprising a screw head (1), a screw body (2), and a screw tail (3), characterized in that: The screw is made of Mg-Zn-Mn alloy, wherein the Zn content is 1.2%-1.8%, the Mn content is 0.05%-0.08%, and the rest is pure magnesium. The surface microstructure of the screw is a continuous fine grain zone formed after rolling treatment. The surface of the screw is provided with a composite coating (4) consisting of a Zn / Mg-HA calcium-phosphorus layer and a parylene layer.
2. A magnesium alloy hollow bone screw and a preparation method thereof according to claim 1, characterized in that: A hollow structure (5) is provided inside the screw body (2) and the screw tail (3), and a screwing groove (6) is provided at the front end of the screw head (1).
3. A method for preparing a magnesium alloy hollow bone screw, based on the magnesium alloy hollow bone screw according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1. Obtaining a magnesium alloy rod-shaped ingot and subjecting it to a thermomechanical treatment to a desired size for processing; S2. rolling the magnesium alloy tube at room temperature to avoid softening of the magnesium alloy; S3. Drilling a hole inside the magnesium alloy screw to a depth equal to the length of the screw to form a hollow hole inside the screw; S4. Clean the magnesium alloy hollow bone screw to remove residues; S5. Prepare a surface treatment solution, wherein the surface treatment solution includes magnesium nitrate hexahydrate, zinc nitrate hexahydrate and calcium nitrate tetrahydrate, EDTA-4NH4, alanine, diammonium hydrogen phosphate, and ammonia water. After the preparation is completed, place the cleaned sample in the treatment solution and heat it in a 60°C water bath for 4-6 hours. After the reaction is completed, take it out and wash it. S6. Depositing another layer of parylene on the surface treatment layer by a deposition method, and then performing a low-temperature annealing treatment to improve adhesion.
4. The method for preparing a magnesium alloy hollow bone screw according to claim 3, characterized in that: The magnesium alloy rod-shaped ingot comprises 1.2%-1.8% Zn, 0.05%-0.08% Mn, and the remainder is pure magnesium.
5. The method for preparing a magnesium alloy hollow bone screw according to claim 3, characterized in that: The rolling temperature is 50-100° C., the rolling force is 3-6 tons, the rolling speed is 0.1-1 mm / min, and dithiophosphate lubricant is selected for rolling. The rolling is performed in one step to ensure the consistency and accuracy of the thread.
6. The method for preparing a magnesium alloy hollow bone screw according to claim 3, characterized in that: When drilling, the tool speed is 600-1200rpm and the feed rate is 0.01-0.1mm / rev.
7. The method for preparing a magnesium alloy hollow bone screw according to claim 3, characterized in that: When preparing, add 0.02-0.18mol / L magnesium nitrate hexahydrate, 0.18-0.02mol / L zinc nitrate hexahydrate and 0.8mol / L calcium nitrate tetrahydrate to water, stir until completely dissolved to form a uniform mixed solution, gradually add 1mol / L EDTA-4NH4 and 2mol / L alanine to the solution and stir until completely dissolved, ensuring that Ca 2+ 、Zn 2+ and Mg 2+ Chelate with EDTA to regulate the release of metal ions, then slowly add the prepared 0.6 mol / L diammonium hydrogen phosphate solution to the mixed solution, maintain a magnetic stirring speed of 100-200 rpm during the addition process to ensure uniform mixing of the solution, and adjust the solution pH to 9-11 with ammonia water to obtain a surface treatment solution.
8. The method for preparing a magnesium alloy hollow bone screw according to claim 7, characterized in that: The surface coating of the surface treatment solution is Zn / Mg-HAP doped with zinc and magnesium, and the compound is Ca 10 -x-yMgxZny(PO4)6(OH)2, wherein the ratio of (magnesium nitrate hexahydrate + zinc nitrate hexahydrate + calcium nitrate tetrahydrate): EDTA-4NH4: alanine: diammonium hydrogen phosphate is 1:1:2:0.
6.
9. The method for preparing a magnesium alloy hollow bone screw according to claim 3, characterized in that: In the surface treatment mixture, the concentration of magnesium nitrate hexahydrate is 0.02-0.19 mol / L, the concentration of zinc nitrate hexahydrate is 0.01-0.05 mol / L, the concentration of calcium nitrate tetrahydrate is 0.8-0.97 mol / L, the concentration of EDTA-4NH4 is 1 mol / L, the concentration of alanine is 2 mol / L, and the concentration of diammonium hydrogen phosphate solution is 0.6 mol / L.
10. The method for preparing a magnesium alloy hollow bone screw according to claim 3, characterized in that: The thickness of the parylene layer is 0.1-1 um.